Addressing feed gap using resilient forage-based feed options and densification: A perspective from Tunisia with wider applicability - Rűdiger, Udo; Peters, Michael; Mwendia, Solomon; Makkar, Harinder P. S.; Hassan, Sawsan; Dey, Bhramar (2024)
In the face of animal feed insecurities, the present perspective focuses on Tunisia and explores the potential of locally available materials - such as, forages and by-products - to increase quality feed supply in the country. Forage production from a mix of forage species (triticale, oats, fenugreek, and vetch) in different proportions to pellet production using a mix of grains of maize, barley and soybean and locally available feed ingredients such as date palm byproducts, grain brans, tomato plant, saline-tolerant local alfalfa, among others are being increasingly used by small and medium farmers. Business models through public-private partnerships that include feed densification technologies like pelletization provide a novel solution to spatially configure feed supply in the north and demand sink in southern Tunisia where agroecological conditions are arid. With appropriate and effective policy and enabling environment, these adaptive strategies that build local resilience have applicability in Tunisia and beyond.